Using trauma-informed approaches: research with climate disaster affected communities - Jo Longman; Jodie Bailie; Petr Matous; Emma Pittaway; Lisa McPhie; Scott Webster; Maddy Braddon; Nader Naderpajouh; Blanche Verlie (BMJ Global Health)
Climate disasters like floods and bushfires have increased in frequency and intensity in Australia. For many, these disasters are associated with trauma. In order to further our understanding of the impacts of these disasters on individuals and communities, we need to conduct research, but the research design and implementation need to be sensitive to that trauma and support the safety of both participants and researchers. This paper provides a detailed description of the practical application of a trauma-informed research approach taken in a study exploring community-led self-organising before, during and after disasters in New South Wales, Australia. The trauma-informed approach was directed by the literature, the university’s ethics committee, a trauma expert, learnings from skills training and guidelines on conducting trauma-informed research offered by Alessi and Kahn. Our team found the approach useful in preparing us for recruitment, data collection, and analysis and dissemination. A culture of care was created which maintained a focus on the well-being of participants as well as providing support for members of the team, in particular from supervision by the trauma specialist. Our paper offers reflections on our experiences, practical suggestions and considerations for planning and conducting research in communities impacted by disasters and elaborations to the Alessi and Kahn guidelines. We conclude by proposing considerations for future directions.